The Transformation of Communal Spirituality: A Phenomenological Study of the Sowing of Religious Literacy and Ideology in Tabbae, Benteng Tellue Village, Bone Regency - Nurhalisa Nurhalisa; Wahyuddin Halim; Darmawati H; Nila Sastrawaty; Asrul Muslim (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study highlights the spiritual transformation experienced by the Tabbaqé community, located in Benteng Tellue Village, Amali District, Bone Regency, known as the "Texas Village." This study aims to understand the transformation that occurs in the community's daily behavior that is influenced by the religious dimension. The type of research used is field research using historical, phenomenological, and ethnographic approaches. This study reveals the background of the formation of negative stigma against the Tabbae community and their self- and collective identity. This study also highlights how the spirituality of the Tabbaqé community both in the past and in the present and the important role of religious leaders in transforming religious life patterns. This study shows that religious literacy plays a significant role in changing the negative stigma attached to the Tabbaqé community using stigma theory. It was found that changes in the community's social identity occurred through a process of negotiation of meaning between individuals and external groups. The previously entrenched stigma began to erode with increased understanding of religion and better spiritual practices. Meanwhile, from the perspective of tazkiyah an-nafs, the spiritual transformation that occurs helps people purify their souls to build collective awareness in living a life that is more based on religious values.